2013
DOI: 10.1038/nature12893
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and virological mechanisms of vaccine-mediated protection against SIV and HIV

Abstract: Summary A major challenge for the development of a highly effective AIDS vaccine is the identification of mechanisms of protective immunity. To address this question, we used a non-human primate challenge model with simian immunodeficiency virus (SIV). We show that antibodies to the SIV Envelope are necessary and sufficient to prevent infection. Moreover, sequencing of viruses from breakthrough infections revealed selective pressure against neutralization-sensitive viruses; we identified a two amino acid signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
199
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(216 citation statements)
references
References 39 publications
16
199
1
Order By: Relevance
“…Nonetheless, partial efficacy observed in the RV144 vaccine trial 4 renewed interest in HIV-1 Env as an immunogen candidate. This was corroborated by a recent study describing that vaccine-elicited anti-Env antibodies were sufficient to generate a certain degree of protection against SIV and HIV challenges 5 .…”
Section: Introductionsupporting
confidence: 55%
“…Nonetheless, partial efficacy observed in the RV144 vaccine trial 4 renewed interest in HIV-1 Env as an immunogen candidate. This was corroborated by a recent study describing that vaccine-elicited anti-Env antibodies were sufficient to generate a certain degree of protection against SIV and HIV challenges 5 .…”
Section: Introductionsupporting
confidence: 55%
“…It should be noted that in an SIVmac challenge study, where SIV (rather than HIV‐1) mosaic Envs were evaluated, no vaccine‐mediated protection by antibodies was observed in the mosaic Env vaccine group, while animals vaccinated with a natural protein showed reduced rates of acquisition 42. The mosaic‐Env‐vaccinated macaques in this study did, however, have lower peak viremia, and reduced viral loads in early infection.…”
Section: T‐cell Vaccine Design Strategiesmentioning
confidence: 57%
“…Moreover, HIV‐1 mosaic Envs undergo the appropriate conformational shift when bound to CD4,36 and so are assumed to form native‐like proteins. However, the SIV mosaics were not similarly evaluated 42. Also of note, SIV Gag mosaic vaccinated animals in this same study had reduced viral load and improved survival upon SIVmac infection 42…”
Section: T‐cell Vaccine Design Strategiesmentioning
confidence: 87%
See 1 more Smart Citation
“…8891 Martins et al 88 reported that vaccine regimens that did not contain Gag, or Env or a combination of both were largely inefficient in reducing viremia, suggesting that the synergy between Gag-specific T cell responses and antibodies targeting Env were an important requirement in the effective control of the virus, an observation also supported by others. 92 , 93 Roederer et al 89 reported that vaccination with mosaic Gag DNA as prime followed by rAd5 as a booster immunization did not protect from infection but showed reduction of viremia. On the other hand, Hansen et al 90 , 91 reported no protection from virus acquisition but found robust control of viremia in ∼half of the rCMV (SIV Gag) immunized macaques.…”
Section: Discussionmentioning
confidence: 99%